2018
DOI: 10.3389/fpsyg.2018.02657
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Eating Behavior: A Daily Diary Study in Youngsters

Abstract: Background: Overweight and obesity are growing problems, with more attention recently, to the role of stress in the starting and maintaining process of these clinical problems. However, the mechanisms are not yet known and well-understood; and ecological momentary analyses like the daily variations between stress and eating are far less studied. Emotional eating is highly prevalent and is assumed to be an important mechanism, as a maladaptive emotion regulation (ER) strategy, in starting and maintaining the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 92 publications
(150 reference statements)
3
35
0
5
Order By: Relevance
“…Emotional eating is a very common eating disorder among youth. It occurs especially in many different emotional conditions related to stress 11 . This study was conducted to determine the effect of sociodemographic characteristics of university students on emotional eating behavior and was discussed with the relevant literature.…”
Section: Discussionmentioning
confidence: 99%
“…Emotional eating is a very common eating disorder among youth. It occurs especially in many different emotional conditions related to stress 11 . This study was conducted to determine the effect of sociodemographic characteristics of university students on emotional eating behavior and was discussed with the relevant literature.…”
Section: Discussionmentioning
confidence: 99%
“…Previous diary-based research has suggested that having more data points per day, as opposed to general daily stress reports, will be better able to capture the relationship between stress and behavior [11]. While these authors suggested that increased reporting could lead to increased burden and decreased willingness in participants, wearable monitoring might nevertheless facilitate data sampling hence decreasing burden.…”
Section: Journal Of Sensorsmentioning
confidence: 99%
“…Additionally, people have a tendency to forget emotional peaks within 24 hours [7]. Diary methods have been used successfully in treatment and research, but often show decreased use over time [10,11]. Wearables could help collect data between sessions that is less subject to bias and such automatic registration could reduce the load and hereby potentially increase adherence to data collection between sessions.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies point to "stress" as an important factor in the development and maintenance of childhood obesity [8,74,79,110]. For example, families with an obese child experience more stress [102], and daily hassles seem to have a significant impact on children's eating behavior [44,110]. However, although the contributing role of stress in obesity is well studied, treatment options have not been developed in response.…”
Section: Introductionmentioning
confidence: 99%